Differential Alterations of the Mitochondrial Morphology and Respiratory Chain Complexes during Postnatal Development of the Mouse Lung. (19th December 2017) - El-Merhie, Natalia; Baumgart-Vogt, Eveline; Pilatz, Adrian; Pfreimer, Susanne; Pfeiffer, Bianca; Pak, Oleg; Kosanovic, Djuro; Seimetz, Michael; Schermuly, Ralph Theo; Weissmann, Norbert; Karnati, Srikanth
Abstract : Mitochondrial biogenesis and adequate energy production in various organs of mammals are necessary for postnatal adaptation to extrauterine life in an environment with high oxygen content. Even though transgenic mice are frequently used as experimental models, to date, no combined detailed molecular and morphological analysis on the mitochondrial compartment in different lung cell types has been performed during postnatal mouse lung development. In our study, we revealed a significant upregulation of most mitochondrial respiratory complexes at protein and mRNA levels in the lungs of P15 and adult animals in comparison to newborns. The majority of adult animal samples showed the strongest increase, except for succinate dehydrogenase protein (SDHD). Likewise, an increase in mRNA expression for mtDNA transcription machinery genes ( Polrmt, Tfam, Tfb1m, and Tfb2m ), mitochondrially encoded RNA ( mt-Rnr1 and mt -Rnr2 ), and the nuclear-encoded mitochondrial DNA polymerase (POLG) was observed. The biochemical and molecular results were corroborated by a parallel increase of mitochondrial number, size, cristae number, and complexity, exhibiting heterogeneous patterns in distinct bronchiolar and alveolar epithelial cells. Taken together, our results suggest a specific adaptation and differential maturation of the mitochondrial compartment according to the metabolic needs of individual cell types during postnatal development of the mouse lung.